Effects of some lubricants and evaluation of compression parameters on directly compressible powders - UĞURLU, TİMUÇİN (TAYLOR & FRANCIS LTD, 2014)
The objective of this study was to investigate the effects of conventional lubricants including a new candidate lubricant Hexagonal boron nitride (HBN) on direct compression powders. Lubricants such as magnesium stearate, glyceryl behenate, stearic acid, talc and polyethylene glycol(6000) were studied in this article. Tablets were manufactured on an instrumented tablet press with various lubricant concentrations. Bulk and tapped densities, and Carr's index parameters were calculated for powders. Tensile strength, cohesion index, lower punch ejection force and lubricant effectiveness values were investigated for tablets. The deformation mechanisms of tablets were studied during compression from the Heckel plots with or without lubricants. Powders formulated with MGST and HBN showed better flow properties based on Carr's index. MGST was found to be the most effective lubricant based on lubricant effectiveness for tablets. HBN was found very close to MGST with the same concentrations. Other lubricants showed less effectiveness than that of MGST and HBN. It is observed that an increase in the concentration of HBN leads to decreased tensile strength and cohesion index values because of its surface-covering property. Despite covering property, HBN had no significant effect on disintegration time. Based on the Heckel plots at the level of 1%, HBN showed the most pronounced plastic character.
Keywords: Cohesion index; direct compression; hexagonal boron nitride; lubricants; lubricant effectiveness; BORON-NITRIDE NANOTUBES; COMPACTION PROPERTIES